The Role of the Interactive Whiteboard in Developing Arabic Writing Skills among Non-Native Speakers - Alamri, Hind Abdullah Muhammad (Journal of Curriculum and Teaching Methodology, 2025)
The goal of this study was to understand the role of the interactive board in improving Arabic writing skills for non-Arab speakers. To achieve this goal, descriptive, observational, and interview methods were used to collect data. The observation checklist was applied to a sample of 18 female students from levels three and four (advanced level), while interviews were conducted with 4 female teachers from the Arabic Linguistics Institute at King Saud University. The results of the study were the following: The Interactive board was evidently effective in improving the writing skills of the students and it functioned well for the institute’s learning goals. Therefore, the study recommends utilizing the interactive board to improve students writing skills and making it available throughout the institute as much as possible.
Keywords: Interactive Whiteboard; Writing Skills; Arabic for Non-Native Speakers